Marine monitoring in Europe: is it adequate to address environmental threats and pressures? - Suzanne J. Painting; Kate A. Collingridge; Dominique Durand; Antoine Grémare; Veronique Créach; Christos Arvanitidis; Guillaume Bernard (Ocean Science, 2020)
We provide a review of the environmental threats and gaps in monitoring programmes in European coastal waters based on previous studies, an online questionnaire, and an in-depth assessment of observation scales. Our findings underpin the JERICO-NEXT1 monitoring strategy for the development and integration of coastal observatories in Europe and support JERICO-RI2 in providing high-value physical, chemical, and biological datasets for addressing key challenges at a European level. This study highlights the need for improved monitoring of environmental threats in European coastal environments. Participants in the online questionnaire provided new insights into gaps between environmental threats and monitoring of impacts. In total, 36 national representatives, scientists, and monitoring authorities from 12 European countries (Finland, France, Germany, Greece, Ireland, Italy, Malta, Norway, Poland, Spain, Sweden, UK) completed the questionnaire, and 38 monitoring programmes were reported. The main policy drivers of monitoring were identified as the EU Water Framework Directive (WFD), the Marine Strategy Framework Directive (MSFD), Regional Seas Conventions (e.g. OSPAR), and local drivers. Although policy drivers change over time, their overall purposes remain similar. The most commonly identified threats to the marine environment were marine litter, shipping, contaminants, organic enrichment, and fishing. Regime change was identified as a pressure by 67 % of respondents. The main impacts of these pressures or threats were identified by the majority of respondents (> 70 %) to be habitat loss or destruction, underwater noise, and contamination, with 60 % identifying undesirable disturbance (e.g. oxygen depletion), changes in sediment and/or substrate composition, changes in community composition, harmful microorganisms, and invasive species as impacts. Most respondents considered current monitoring of threats to be partially adequate or not adequate. The majority of responses were related to the spatial and/or temporal scales at which monitoring takes place and inadequate monitoring of particular parameters. Suggestions for improved monitoring programmes included improved design, increased monitoring effort, and better linkages with research and new technologies. Improved monitoring programmes should be fit for purpose, underpin longer-term scientific objectives which cut across policy and other drivers, and consider cumulative effects of multiple pressures. JERICO-RI aims to fill some of the observation gaps in monitoring programmes through the development of new technologies. The science strategy for JERICO-RI will pave the way to a better integration of physical, chemical, and biological observations into an ecological process perspective.

Toward a European Coastal Observing Network to Provide Better Answers to Science and to Societal Challenges; The JERICO Research Infrastructure - Patrick Farcy; Dominique Durand; Guillaume Charria; Suzanne J. Painting; Timo Tamminen; Kate Collingridge; Antoine J. Grémare; Laurent Delauney; Ingrid Puillat (Frontiers in Marine Science, 2019)

Optimizing Monitoring Programs: A Case Study Based on the OSPAR Eutrophication Assessment for UK Waters - Luz María García-García; Dave Sivyer; Michelle Devlin; Suzanne Painting; Kate Collingridge; Johan van der Molen (Frontiers in Marine Science, 2019)